Clinical implications and characterization of Group A Streptoccoccus infections in adults with cystic fibrosis. Issue 1 (December 2015) - Skolnik, Kate; Nguyen, Austin; Somayaji, Ranjani; Thornton, Christina; Waddell, Barbara; Surette, Michael; Rabin, Harvey; Parkins, Michael
Abstract Background Persistent airway infection is a hallmark feature of cystic fibrosis (CF). However, increasingly it has been observed that non-classical pathogens may transiently infect CF lower airways.Streptococcus pyogenes (Group A Streptococcus; (GAS)) is an uncommon but potentially dangerous cause of community-acquired pneumonia. Our aim was to determine the incidence, natural history, and clinical impact of GAS infections in CF and phenotypically and genotypically characterize the isolates. Methods We retrospectively evaluated the Calgary Adult CF Clinic biobank to identify adults with at least one GAS isolate. Patient demographics, medical and pulmonary exacerbation (PEx) histories were evaluated. The primary outcome was PEx occurrence at incident GAS culture. Secondary outcomes evaluated were changes in lung function and PEx frequency following GAS isolation. Isolates were assessed for extra-cellular virulence factor production capacity and ability to produce quorum sensing (AI-2). Isolates were genotyped using pulse-field gel electrophoresis (PFGE). Results Fifteen individuals who cultured GAS twenty times were identified. At the time of GAS isolation, 47 % (7/15) of subjects experienced a PEx and half of these (4/7) were severe. Individuals were more likely to have a PEx at the time of the index GAS isolate compared to the preceding visit (RR = 6.0, 95 % CI 0.82–43.0, p = 0.08), particularly if GAS was the numerically dominant sputum pathogen (RR = 6.5, 95 % CI 1.00–43.0, p = 0.009). There were no changes in PEx frequency or rate of lung function decline following GAS. None of the patients developed chronic airways infection, bacteremia, necrotizing pneumonia or empyema. Susceptibility was universal to common anti-Streptococcal antibiotics and anti-Pseudomonal antibiotics commonly used in CF, with the exception of azithromycin. GAS isolates varied in their production of protease, DNase, and AI-2 but these did not correlate with PEx, and none produced elastase, chrondrotin sulfatase or H2 02 . One patient had prolonged carriage with the same isolate and two patients had isolates with similar PFGE patterns. Conclusions GAS was an uncommon lower respiratory pathogen of adults with CF. Identification of GAS in sputum was frequently associated with PEx, particularly when numerically dominant. However, transient GAS infection did not result in chronic infection nor appreciably change long-term disease trajectory.